PENGARUH PEMANFAATAN DANA ZAKAT PRODUKTIF TERHADAP TINGKAT PENDAPATAN MUSTAHIK PADA PROGRAM Z-MART DI BAZNAS KABUPATEN BANDUNG BARAT - Dennita Oktatiara; Saepul Ma’mun; Rahmat Nur Ramdan (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2026)
Zakat is an important instrument in the Islamic economic system that plays a significant role in reducing poverty and improving the welfare of the Muslim community, one of which is through productive zakat. This study is motivated by the influence of the utilization of productive zakat funds on the income level of mustahik in the Z-Mart program managed by BAZNAS of West Bandung Regency. The purpose of this study is to examine and analyze whether the utilization of productive zakat funds can increase the income of mustahik who beneficiaries of the Z-Mart program are. This study employed a quantitative approach using a survey method through questionnaires distributed to a sample of 60 respondents selected from a population of 151 mustahik using a purposive sampling technique. The results of the validity and reliability tests indicated that the research instruments were valid and reliable. Simple linear regression analysis showed that the utilization of productive zakat funds had a positive effect on the income of mustahik, with a coefficient of determination (R²) of 77.5%. The partial test (t-test) revealed that the calculated t-value of 14.146 was greater than the t-table value of 1.671, with a significance level of less than 0.05. Therefore, H₀ was rejected and Hₐ was accepted. In conclusion, the utilization of productive zakat funds has a significant positive effect on increasing the income of mustahik participating in the Z-Mart program of BAZNAS West Bandung Regency.